Neo‐ and Paleopolyploidy contribute to the species diversity of Asplenium—the most species‐rich genus of ferns. Issue 4 (21st July 2017) - Schneider, Harald; Liu, Hong‐Mei; Chang, Yan‐Fen; Ohlsen, Daniel; Perrie, Leon R.; Shepherd, Lara; Kessler, Michael; Karger, Dirk N.; Hennequin, Sabine; Marquardt, Jeannine; Russell, Stephen; Ansell, Stephen; et al.
Abstract: Polyploidy is widely considered as a major process in the evolution of plants but the accumulation of polyploid species diversity is still controversial. Some recent studies proposed increased extinction risk in neopolyploids compared with their diploid ancestors. The high proportion of polyploid ferns is expected to be formed mainly by neopolyploids, whereas paleopolyploid species are predicted to be clustered in clades founded by whole genome duplications. Here, we test this prediction by exploring the evolution of polyploidy in the derived fern family Aspleniaceae. The family has a global distribution and shows the highest frequency of polyploid taxa among all ferns. To test the hypothesis, we obtained a comprehensive phylogeny using chloroplast DNA sequences of 883 specimens representing 292 species. All published chromosome counts were mapped onto this phylogenetic framework in order to explore the evolution of polyploids. We recovered evidence for several whole genome duplications in the history of Aspleniaceae. Phylogenetic relationships of polyploids exceeding the tetraploid level suggest that tetraploid Asplenium species may have replaced their diploid ancestors as the main evolutionary players in some clades of this family.